Curriculum Development To Improve Arabic Language Skill In The Institute Of Umul Qro Al-Islam (IUQI), Bogor And The Islamic Religious Institute Of Sahid (INAIS) Bogor - Uwoh Abdullah; Badruzzaman M. Yunus; Izzuddin Musthafa; Isop Syafe’i (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Curriculum is the core of the field of education and has an influence on all educational activities. Given the importance of curriculum in education and human life, the preparation of curriculum can not be done carelessly. The preparation of the curriculum requires strong foundations, which are based on the results of in-depth thinking and research. The curriculum of PT is an institutional mandate that must be constantly updated in accordance with the development needs set forth in the learning achievements. This study aims to determine: 1) the condition of curriculum development in improving Arabic language skills, 2) design of curriculum development in improving Arabic language skills, 3) implementation of curriculum development in improving Arabic language skills, 4) the effectiveness of curriculum development in improving Arabic language skills, and 5) the success of curriculum development in improving Arabic language skills at the Ummul Quro Al-Islami Institute (Iuqi) and the Sahid Islamic Institute (Inais) Bogor. This research uses research and Development (R&D) method with research design includes: preliminary study, development, and testing results (validation). Data was collected through interviews, observations, tests and documentation studies, with data sources obtained from curriculum experts, field practitioners, and students. Data analysis was done by quantitative experiments through the design of one group pretest-posttest between the experimental group (using modules) with the control group (without modules). The results of the study were: 1) the condition of curriculum development in both universities in terms of 2 aspects, namely: Faculty ability, management of Arabic learning, student interest, facilities, facilities and Environment; 2) the design of the curriculum developed includes Arabic learning objectives, materials, learning techniques and evaluation to improve Arabic language skills; 3) implementation of curriculum development in both universities is implemented; 4) the effectiveness of curriculum development in both universities after the implementation of the developed Arabic curriculum can be identified that the Arabic curriculum used is more effective in improving students ' Arabic language skills when compared to the Arabic curriculum that has not been developed; 5) the success of curriculum development in both universities is obtained from the results of curriculum development in; providing support to the task of lecturers, especially facilitate lecturers in preparing learning plans, implementing learning, and evaluating learning outcomes.